Innate immune detection of microbial nucleic acids - BOWIE, ANDREW (My University, 2013)
Detection of pathogen-derived nucleic acids by pattern recognition receptors (PRRs) is essential for the host to mount an appropriate immune response, which for viruses involves the induction of type I interferons (IFNs). By contrast, inappropriate activation of PRRs by self nucleic acids can lead to autoimmunity. Recent developments in PRR research have uncovered important new molecular details as to how Toll-like receptors (TLRs) and retinoic acid-inducible gene-I (RIG-I)-like receptors (RLRs) distinguish pathogen from self RNA, while the discovery of cytosolic DNA sensing pathways for IFN induction has revealed completely new innate signaling mechanisms, and also questions how innate immunity discriminates between self and non-self DNA, if at all.
PUBLISHED
Keywords: cytosolic DNA sensing; antiviral immunity; RIG-I; STING; Toll-like receptors; Immunology, Inflammation & Infection